2023
DOI: 10.1108/tqm-07-2022-0243
|View full text |Cite
|
Sign up to set email alerts
|

Integration of Lean manufacturing and Industry 4.0: a bibliometric analysis

Abstract: PurposeThe purpose of this study is to identify the prominent research constituents in the domain of integration of Lean manufacturing and Industry 4.0 techniques and analyze the intellectual structure among them.Design/methodology/approachA bibliometric analysis of articles based on Donthu et al. (2021a) has been adopted to conduct a systematic review of the integration of Lean manufacturing and Industry 4.0 using the Scopus database.FindingsThe co-citation analysis and bibliographic coupling depicted three c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
13
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 27 publications
(13 citation statements)
references
References 112 publications
0
13
0
Order By: Relevance
“…, 2021; Rossini et al ., 2019; Mokudai et al. , 2021; Holmemo and Korsen, 2023; Kumar et al. , 2023; Von Haartman et al.…”
Section: Theoretical Frameworkmentioning
confidence: 99%
“…, 2021; Rossini et al ., 2019; Mokudai et al. , 2021; Holmemo and Korsen, 2023; Kumar et al. , 2023; Von Haartman et al.…”
Section: Theoretical Frameworkmentioning
confidence: 99%
“…As presented in Table 1, the study of Kumar et al (2022) was the only paper found that used a network representation to verify synergies between Lean and Industry 4.0. That said, unlike the present work, the authors' goal was to identify prominent research constituents in the domain of integration between both topics.…”
Section: Network Theory and Applicationsmentioning
confidence: 99%
“…The fast pace of technological development is causing profound changes in the way of living and working, in addition to impacting all areas of knowledge, economies and industries (MDIC and MCTIC, 2016). It can be argued that Industry 4.0 technologies, also described as digital manufacturing and smart manufacturing technologies, have a major role in this regard, as they are attracting increasing attention across global manufacturing setups (Kumar et al, 2022). Moreover, it is possible to notice that many companies, especially in industrial sectors, seek to apply the latest Industry 4.0 trends combined with Lean manufacturing concepts to remain competitive (Kolla et al, 2019).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Both OPEX and I4.0 share common goals related to improvement in profitability dynamics, employee performance and waste reduction. However, the integration of I4.0 with OPEX to gain strategic benefits in terms of improvement in different quality, ecology and social sustainability metrics (Kumar et al ., 2024) has not been explored much in the academic literature. This Special Issue (SI) attempts to address the unexplored aspects related to I4.0 and OPEX strategies together.…”
mentioning
confidence: 99%